(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: This study aimed to prove the effects of Escherichia coli isolates isolated from diseased broilers to form biofilms, describe their antimicrobial sensitivity, and determine the effect of allicin and cinnamon essential oils on the expression of some genes (fimH, int1, and luxS) through quantitative polymerase chain reaction (q-PCR). Materials and Methods: 140 samples were obtained from diseased broilers in Beni-Suef Governorate, Egypt. These samples were examined by conventional bacteriology methods to detect the causative agent. The antimicrobial susceptibility of the isolated bacteria was assessed using the disc diffusion method, The ability of yeast extract-casamino acids Congo Red Agar to generate phenotypic biofilms was next tested. The presence of resistance and virulence genes in some multidrug resistant isolates was genotypically investigated. The antibacterial effects of allicin and cinnamon oil were evaluated against the growth of multidrug-resistant E. coli. Finally, q-PCR was utilized to assess changes in some genes’ expression. Results: Escherichia coli was isolated from 61 samples(43.6%). An antimicrobial susceptibility test revealed that multidrug-resistance (MDR) (could resist more than three antimicrobial classes) E. coli prevalence was 100%. 40.8% of isolates phenotypically produce biofilms. The detection of resistance and virulence genes by PCR showed that all tested isolates carry aadB, fimH, int1, qnrS, and luxS genes, while only 40% harbor is genes. q-PCR showed that after treatment with allicin and cinnamon oils, gene expression went down. Conclusion: This investigation highlights that E. coli showed resistance against most of the tested antimicrobials; all isolates were MDR. The study showed wide dissemination of virulence and resistance genes among E. coli. Allicin and cinnamon oils have antimicrobial activities and could be used as alternatives to synthetic antimicrobial agents. J. Adv. Vet. Anim. Res., 9(2): 191–202, June 2022 http://doi.org/10.5455/javar.2022.i584